HIF-PH Encoded by EGLN1 Is a Potential Therapeutic Target for Chronic Lymphocytic Leukemia - Wancheng Guo; Daomiao Liang; Peilong Wang; Le Yin; Huifang Zhang; Cheng Xing; Zineng Huang; Yinghua Wu; Heng Li; Zhao Cheng; Xiaojuan Xiao; Jing Liu; et al. (MDPI AG, 2022)
Owing to the recent emergence of drug resistance to Bruton's tyrosine kinase inhibitors (BTK) in chronic lymphocytic leukemia (CLL) treatment, it is crucial to identify alternative therapeutic targets. Therefore, we aimed to identify therapeutic options for CLL besides BTK. We identified that HIF1A expression was higher in CLL patients than in controls, which may suggest good prognosis. We used a lentiviral knockdown of EGLN1 (encoding hypoxia-inducible factor prolyl hydroxylase [HIF-PH]) and found that the growth of MEC-1 cells slowed in the knockdown group. Treatment of CLL cell lines MEC-1 and HG3 with the HIF-PH inhibitor molidustat showed that molidustat could induce apoptosis in a concentration-dependent manner in CLL cells and had low cytotoxicity at this concentration. CXCR4, HIF1A, SLC2AI, and VEGF, the downstream molecules of the HIF pathway, were upregulated after molidustat treatment. Western blotting results indicated that molidustat increased HIF1A expression in CLL cell lines and cells from CLL patients, and sequencing/quantitative PCR analysis demonstrated that the ribosome biogenesis pathway was inhibited in MEC-1 cells after molidustat treatment. We further identified synergistic cytotoxicity of molidustat in combination with ibrutinib on the MEC-1 and HG3 cell lines at certain concentrations. Therefore, molidustat is a potential therapeutic option for CLL.